2020
DOI: 10.1002/iid3.335
|View full text |Cite
|
Sign up to set email alerts
|

The pivotal roles of neddylation pathway in immunoregulation

Abstract: Introduction Protein neddylation, one of the most important posttranslational modifications that tagging neuronal precursor cell‐expressed developmentally downregulated protein 8 onto substrate proteins, plays fundamental roles in the process of many cellular functions. A number of studies have demonstrated the critical roles of neddylation modification in multiple pathophysiological processes, but its regulatory role in the immune system has only been finitely unveiled. Methods In this review, the latest adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…As the main pathway of protein degradation, ubiquitination and its new forms have been well studied. Neddylation, a ubiquitination-like modification, has been shown to participate in a large variety of cellular processes and to be involved in modulating cell-cell and cell-microenvironment interactions ( 9 , 10 ), for example, immune-related conditions including inflammation and cancer ( 11 ). Previous works also showed that neddylation plays a significant role in mammalian oocyte maturation and early embryonic development ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the main pathway of protein degradation, ubiquitination and its new forms have been well studied. Neddylation, a ubiquitination-like modification, has been shown to participate in a large variety of cellular processes and to be involved in modulating cell-cell and cell-microenvironment interactions ( 9 , 10 ), for example, immune-related conditions including inflammation and cancer ( 11 ). Previous works also showed that neddylation plays a significant role in mammalian oocyte maturation and early embryonic development ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, many researchers have described the relevant role of the post-translational modification (PTM) known as neddylation in the activation of the immune response and regulation of viral infections [ 7 ]. Neddylation is a reversible PTM characterized by the covalent conjugation of a small peptide NEDD8 (neuronal precursor cell-expressed developmentally downregulated protein 8) to lysine of target proteins in order to modulate their stability, localization, activity and function [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The neddylation process is a highly conserved PTM that allows the cell to respond and adapt quickly and efficiently to various stimuli [ 10 ]. Under physiological conditions, neddylation levels are low, but overactivation of neddylation takes place as a response to cellular stress or DNA damage [ 11 , 12 ], such as during a viral infection, inflammation, or cancer [ 7 , 13 15 ], changing the proteome homeostasis and affecting the metabolism and functionality of the immune cells [ 7 , 16 ]. In fact, a pharmacological inhibitor, MLN4924, was developed which selectively acts on NEDD8 activating enzyme 1 (NAE1) by forming covalent adducts and inhibiting its activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neddylation is a post-translational modification that adds a ubiquitin-like protein, NEDD8 (neuronal precursor cell-expressed developmentally downregulated protein 8), to selected substrate proteins, affecting their stability, conformation/function, and subcellular localization; this in turn can regulate many biological and pathological processes, including cancer progression and immune response [ 1 4 ].…”
Section: Introductionmentioning
confidence: 99%